Rancang Bangun Aplikasi Verifikasi Keaslian e-Sertifikat dengan Algoritma SHA-512 - Javier, J; Dinata, Yuwono Marta (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
In today's digital age, electronic certificates, also known as e-certificates, are frequently used. The authenticity of these certificates, however, can be a challenge to resolve because they are easily falsified. Rarely do certificates for events like contests, seminars, courses, and awards have serial numbers, barcodes, or QR scanners as authenticity markers. Contrary to certificates for land titles, vehicles, law, education, or academia, which are challenging to counterfeit because they have an indicator and typically have a physical form rather than a digital one. Recruiting committees, institutional memberships, and HR departments could all suffer as a result. Therefore, a solution is required to maintain the validity of these certificates using the Cryptographic Hash Function technique and the SHA-512 algorithm, which is the most recent member of the SHA-2 generation. The findings from this research indicate that the website application developed performs effectively on the user's device and facilitates the verification process of e-certificates that lack authenticity indicators. Therefore, the authors can conclude that this website application provides assistance to both individual and organizational users in verifying digital certificates.